2002
DOI: 10.1161/01.cir.0000033826.52681.37
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Deletion of Angiotensin II Type 2 Receptor Caused Cardiac Rupture After Acute Myocardial Infarction

Abstract: Background-Accumulating evidence has suggested that the cardiac renin-angiotensin system is activated during the remodeling process after myocardial infarction (MI). Although 2 types of angiotensin II receptors (AT 1 and AT 2 ) are upregulated in the infarcted tissue, the contribution of AT 2 to the subsequent fibrogenetic phase of wound healing is less certain. This study was conducted to evaluate the role of AT 2 in wound healing after MI using an in vivo intervention study in mice with MI. Methods and Resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
82
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(83 citation statements)
references
References 39 publications
0
82
1
Order By: Relevance
“…Previous basic studies suggested that inhibition of plasminogen activators, MMPs, 9 or cardiac overexpression of FrzA can prevent cardiac rupture, 10 whereas deletion of angiotensin AT 2 receptor can aggravate it. 11 However, the upstream regulators of the genes that trigger these responses have not been studied. TNF-␣ is a master cytokine that is produced in significant quantities within the infarcted myocardium very soon after MI.…”
Section: Discussionmentioning
confidence: 99%
“…Previous basic studies suggested that inhibition of plasminogen activators, MMPs, 9 or cardiac overexpression of FrzA can prevent cardiac rupture, 10 whereas deletion of angiotensin AT 2 receptor can aggravate it. 11 However, the upstream regulators of the genes that trigger these responses have not been studied. TNF-␣ is a master cytokine that is produced in significant quantities within the infarcted myocardium very soon after MI.…”
Section: Discussionmentioning
confidence: 99%
“…24,25,30,33,34 Fifth, although a 2-to 3-fold increase in myocardial collagen above the normal level results in increased LV stiffness and mild dysfunction, 35 a very small decrease in collagen below normal can lead to drastic consequences, 36,37 including LV dilation 4,22,34 and rupture. 33,38 In reperfused MI, decreased or damaged ECCM in the IZ 5,12,39 is associated with cardiac rupture. 5,39 Key Points to Remember About Pathobiology of Cardiac ECCM First, nearly 75% of the cells in the healthy heart are nonmyocytes, which include fibroblasts 18,21 that account for 90% to 95% of nonmyocyte cell mass 17,20,21 (Table 1).…”
Section: Ventricular Remodeling After MI and The Role Of Eccmmentioning
confidence: 99%
“…AngII type 2 (AT 2 ) receptors, which are re-expressed after MI and upregulated in heart failure, are more abundant in human than in rat hearts, are expressed in fibroblastlike cells, and mediate fibrosis, 7,49 and AT 2 loss prevents collagen deposition and causes cardiac rupture. 38 …”
Section: Jugdutt Ventricular Remodeling Postinfarction and The Eccmmentioning
confidence: 99%
“…Rupture is often associated with a transmural infarction, no prior history of angina pectoris, and a relatively large Q-wave infarct, and patients are predisposed to cardiac rupture by systemic and local factors such as hypertension, undue physical activity, diabetes, cardiac hypertrophy, and infarct expansion (1). Although the relevance of these risk factors remains undetermined, accumulated lines of evidence have suggested that disruption of ECM structures such as the collagen network in the infarcted myocardium leads to cardiac rupture (2)(3)(4)(5).…”
Section: Introductionmentioning
confidence: 99%